18 Brief engagement and acceptance coaching in community and hospice settings (the beaches study): protocol for developing and pilot testing an evidence-based intervention to enhance wellbeing at transition into palliative care. Issue 3 (1st September 2018) - Hulbert-Williams, Nick; Gillanders, David; Finucane, Anne; Millington, Susan; Norwood, Sabrina; Spiller, Juliet; Strachan, Jenny; Swash, Brooke
Abstract : Introduction: The transition into palliative care can cause uncertainty fear and distress. Quality of life can be detrimentally affected and advance planning for end-of-life is often avoided. Acceptance and Commitment Therapy (ACT) is a promising intervention for supporting palliative patients; the focus on values may be especially relevant to restoring meaningful living. We present a protocol for development and piloting of a brief ACT-based intervention for delivery at the palliative care transition point. Aims and methods: A multiple-baseline single-case non-controlled design is used. This enables exploration of effectiveness and processes causing outcome improvement. Integrated qualitative interviews provide acceptability data. The five-session intervention is delivered by psychologists to 14 participants in two hospices. Participants with an incurable cancer diagnosis but life expectancy of four months or more are eligible. Weekly self-report questionnaires assess study outcomes (quality of life distress) and changes in therapeutic processes. A smartphone app facilitates daily assessment of brief measures to enable sensitive measurement of process change. Results: Quantitative data will be analysed using visual plots and statistical change indices across study phases: this enables calculation of indicative effect sizes for future trial planning. Recruitment attrition and engagement will be analysed descriptively as feasibility indicators. Framework analysis is used to for qualitative data. Conclusions: Single-case designs are not commonly used in psychosocial oncology however they offer a scientific data-driven approach to intervention development. By the end of this study we aim to manualise our intervention for non-psychologist delivery to plan a randomised trial with maximised implementation potential. References: . Hayes SC, Strosahl KD, Wilson KG. Acceptance and commitment therapy: The process and practice of mindful change 2011. Guilford Press. . Murray, et al. Patterns of social psychological and spiritual decline toward the end of life in lung cancer and heart failure. Journal of Pain and Symptom Management2007;34(4):393–402. . Ost L. The efficacy of acceptance and commitment therapy: An updated systematic review and meta-analysis. Behaviour Research and Therapy2014;61:105–12.